Study on Effect of the Industrial area on Air pollution of the Bilaspur district (International Journal of Food and Nutritional Sciences, 2022)
The industrial area in Bilaspur district has a significant impact on the air quality of thedistrict. The industries emit a variety of pollutants, including particulate matter, sulfurdioxide, nitrogen oxides, and hydrocarbons.